E-Service Quality and Its Impact on User Satisfaction and Loyalty in Online Education - Rafiah, Kurnia Khafidhatur; Revinzky, Muhammad Aqshel (Riwayat: Educational Journal of History and Humanities, 2025)
The rapid expansion of digital education platforms has changed how students access learning materials, making the quality of e-services, user satisfaction, and loyalty essential for maintaining user engagement. This study examines these connections within the framework of the XYZ online learning platform, which aims to support academic achievement for high school and pre-university students. Data were gathered from 219 participants through a structured survey, and the relationships among the variables were analyzed using structural equation modeling (SEM). The results show that the quality of e-services has a significant impact on user satisfaction ( = 0.749, t = 12.372, p 0.05), with efficiency being the most influential factor. However, the direct link between e-service quality and e-loyalty was not significant ( = 0.101, t = 1.289, p 0.05), indicating that user satisfaction fully mediates this connection ( = 0.530, t = 9.021, p 0.05). These findings highlight the crucial role of user satisfaction in promoting loyalty behaviors, such as repeat usage, a willingness to pay more, and positive referrals. Although satisfaction ratings were high, issues related to reliability, privacy, and merchandising were noted, suggesting areas for strategic enhancement. Recommendations for improvement include bolstering system reliability, implementing flexible pricing strategies, encouraging emotional engagement, and utilizing user feedback for ongoing service optimization. This research adds to the growing knowledge base on digital education by emphasizing practical strategies for enhancing user retention and engagement.